Communication at Microsoft Services Asia (A) - ANG, Jovina (Institutional Knowledge at Singapore Management University, 2012)
The global financial crisis of 2009 affected Microsoft’s business adversely, with the services business in Asia contracting by more than 20%. In July 2009, there was a major re-organisation at Microsoft Services Asia as a result of business slowdown. Headcount was cut by 20%, and many employees, especially the consulting staff, were made redundant in a first ever company-wide reduction-in-force. Change management during the reduction-in-force was executed swiftly. Information about the organisational restructure and affected employees was tightly controlled, and communication from senior leadership was not widely practised. Morale was low; there was little communication from the top, and three area general managers were replaced from outside Microsoft. Cassandra Lee was appointed director of marketing communications of Microsoft Services Asia in January 2010. She was tasked to develop a plan to address employee morale and engagement. Case A provides an opportunity for students to use their creativity to think outside-the-box in developing an effective change management plan to address employee morale and align employees to the new services mission, of which effective communication and community building are critical and salient components for success.